Sierra Leone : Strategic Options for Public Sector Reform - World Bank (Washington, DC, 2013)
The purpose of this paper is to outline strategic options for the reform of the public sector. The strategic options will be based upon an analysis of the public sector emerging from the civil war, and a longer period of deterioration and decline. The strategy will be expressed in very broad-brush form; detailed planning will only be possible once the basic strategic decisions have been taken. Years of corrupt, and ineffective government, causing - as well as compounded by - civil war, have left Sierra Leone with poor access to basic services, especially outside Freetown, with substantial dependence on NGOs. Expenditure management is weak; there is no effective accountability; human capacity is weak throughout the public service; and, the management of policy, and programs is highly centralized in Freetown, and in the Office of the President, and the Ministry of Finance. Nonetheless, there is now a strong consensus in favor of reforming the policy process, expenditure management, and accountability. And, there is an ever stronger determination to decentralize the delivery of basic services. The "options" concern the rate of decentralization. But, there is little worldwide experience to suggest that rapid devolution can work in terms of improving service delivery. Sierra Leone will need to be creative about the capacity issue: capacity does not have to be produced by the public sector, but capacity existing elsewhere can be effectively utilized by the public sector. So the recommended option is to act aggressively to build capacity to support the soon-to-be newly elected local councils. And to be sure to allocate the funds needed to support their responsibilities for basic service delivery, which would be expanded as the councils demonstrate their capacity to perform.